Keberlanjutan Kampung Wisata di Masa Pandemi Covid – 19 (Studi Kasus : Kampung Jamur, Desa Wadungasih, Sidoarjo) - Firdha Ayu Atika; Esty Poedjioetami (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
Sidoarjo Regency Government has made many efforts to make the mushroom village more famous and attract tourists to visit. So that efforts are needed to revive Home Based Enterprise (HBE) / household businesses and oyster mushroom cultivation centers, to continue to be the pride of Sidoarjo Regency. The HBE concept supports the economic aspect in realizing Sustainable Development. This can be achieved by realizing environmental integration, socio-cultural interests and maximizing local economic benefits. Of course, the existence of HBE supports the concept of Sustainable Tourism, which can increase people's income in accessing jobs and getting good services in the housing sector. This study uses a mixed method with a combination of quantitative and qualitative. This research begins by collecting information or data in the field. Data collection techniques used in this study include field observations, in-depth interviews and documentation of activities. To support the sustainability of the village, it is necessary to revive marketing facilities in the form of cafes or restaurants that support mushroom village tourism. In addition, the institution that oversees the mushroom cultivation and processed products also needs to be added to control the business management system. The existing environment needs to be improved by adding street furniture elements that support the image of a tourist village. Tourist villages must also be supported by the latest technology to support HBE production. Political relations with government and business CSR can also develop the business of the mushroom village HBE, in helping to invest in capital and equipment.